Radio Colouring of Some Graphs - A. Vimala Rani (Mathematics and Computer Science: Research Updates Vol. 2, 2025)
Radio colouring is a mathematical model of networks. The solution of frequency assignment problem can be analyzed by radio colouring. Radio colouring was defined by Kalfakakou et al. (2003) in 2003 and an approximation algorithm has been discussed. A radio colouring is defined as colouring the vertices of G with positive integers in order that the distance two vertices are assigned different colours and adjacent vertices are coloured with difference at least two. A radio colouring that make use of k-colours is a k-radio colouring. The minimum number of colours used is the radio chromatic number rn(G). In this chapter the radio number of some acyclic graphs like path, comb, caterpillar and star graphs are analyzed. Also it has been discussed for some cyclic graphs like cycle and sunlet graph in second section.